A Correlational-Comparative Study of Kindergarten 1 Students’ and Their Parents’ Perceptions of Parental Encouragement for Learning English at Panaya Phatthanakan School, Bangkok, Thailand - Flood, Patrick Daniel; Eamoraphan, Suwattana (Scholar: Human Sciences, 2020)
This study investigated the relationship and significant differences between students’ and parents’ perceptions of parental encouragement for learning English at Panaya Phatthanakan School, Bangkok, Thailand during the 2018 academic year. The research study focused on four objectives: 1) to determine the level of Kindergarten 1 students’ perceptions of parental encouragement for learning English, 2) to determine the level of parents’ of Kindergarten 1 students’ perceptions of parental encouragement for learning English, 3) to determine if there is a significant relationship between Kindergarten 1 students’ and their parents’ perceptions of parental encouragement for learning English, and 4) to determine if there is a significant difference between Kindergarten 1 students’ and their parent’s perception of parental encouragement for learning English. The instrument used in this study was a perceptions of parental encouragement questionnaire given to 56 Kindergarten 1 students and one parent of each of the students. The research found that both students and parents had a very high level of perceptions of parental encouragement. Correlation analysis showed that there was no significant relationship between the students’ and parents’ perceptions of parental encouragement for learning English. Further, the study found that there was a significant difference between Kindergarten 1 students’ and their parents’ perceptions of parental encouragement at Panaya Phatthanakan School, Bangkok, Thailand.